Trigonometry [disket] (Derbyshire, Eng. : Topclass Technology, 1989)
Module 3.1. Circular measure - radian -- Module 3.2. The six trigonometrical ratios -- Module 3.3. Sine and cosine rules -- Module 3.4. Solutions of triangles in two and three dimensions -- Module 3.5. sin(A+B) cos(A+B) tan(A+B) -- Module 3.6. sin X, cos X, tan X in terms of tan x/2 -- Module 3.7. Solving trigonometrical equations